Sojourn time of almost semicontinuous integral-valued processes in a fixed state - Gusak, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
Let $\xi(t)$ be an almost lower semicontinuous integer-valued process with the moment generating function ofthe negative part of jumps $\xi_k : \textbf{E}[z^{\xi_k} / \xi_k < 0] = \frac{1 − b}{z − b},\quad 0 ≤ b < 1.$ For the moment generating function ofthe sojourn time of $\xi(t)$ in a fixed state, we obtain relations in terms of the roots $z_s < 1 < \widehat{z}_s$ of the Lundbergequation. By passing to the limit $(s → 0)$ in the obtained relations, we determine the distributions of $l_r(\infty)$.